Anaplasma phagocytophilum Ankyrin A Protein (AnkA) Enters the Nucleus Using an Importin-β-, RanGTP-Dependent Mechanism - Kim, Yuri; Wang, Jianyang; Clemens, Emily G.; Grab, Dennis J.; Dumler, J. Stephen (Frontiers in Cellular and Infection Microbiology, 2022)
Anaplasma phagocytophilum, a tick-borne obligately intracellular bacterium of neutrophils, causes human granulocytic anaplasmosis. Ankyrin A (AnkA), an effector protein with multiple ankyrin repeats (AR) is injected via type IV-secretion into the host neutrophil to gain access to the nucleus where it modifies the epigenome to promote microbial fitness and propagation. AR proteins transported into the host cell nucleus must use at least one of two known eukaryotic pathways, the classical importin β-dependent pathway, and/or the RanGDP- and AR (ankyrin-repeat)-dependent importin β-independent (RaDAR) pathway. Truncation of the first four AnkA N-terminal ARs (AR1-4), but not other regions, prevents AnkA nuclear accumulation. To investigate the mechanism of nuclear import, we created point mutations of AnkA N-terminal ARs, predicted to interfere with RaDAR protein import, and used importazole, a specific inhibitor of the importin α/β, RanGTP-dependent pathway. Nuclear colocalization analysis shows that nuclear localization of AnkA is unaffected by single AR1-4 mutations but is significantly reduced by single mutations in consecutive ARs suggesting RaDAR protein nuclear import. However, AnkA nuclear localization was also decreased with importazole, and with GTPγS. Furthermore, A. phagocytophilum growth in HL-60 cells was completely suppressed with importazole, indicating that A. phagocytophilum propagation requires a β-importin-dependent pathway. A typical classical NLS overlapping AR4 was subsequently identified suggesting the primacy of the importin-α/β system in AnkA nuclear localization. Whether the mutational studies of putative key residues support RaDAR NLS function or simply reflect structural changes that diminish engagement of an AR-NLS-importin pathway needs to be resolved through careful structure-function studies.